The Study of Teachers’ Activity in Vocational Education as a Scientific Problem - Aleksandrova, Natalia Mikhaylovna; Guseva, Polina Vadimovna (International Review of Management and Marketing, 2016)
The article presents the results of the study of activity of teachers of vocational education from the standpoint of the section of Professional Pedagogy – Professiology of vocational education. The following methods of the study were used: observation of activity of teachers and students during classes, questioning teachers and conversations with them. The study involved teachers of secondary and higher vocational education institutions. A comparative analysis of professional activity of teachers of higher vocational education in two directions of education was conducted: the first one – art, namely, “Applied and Decorative Arts and Folk Crafts”, profile “Lacquer miniature painting on papier-mache”; the second one – pedagogical, namely, “Vocational training (by field)”, profile “Economics and management”. The analysis data of professional activity of teachers of secondary vocational education, carried out by the same art direction and profile, was represented. Besides, the results of the study of the professional activity of teachers of secondary vocational education institutions, which train future skilled workers, employees and mid-tier professionals, mostly in technical major, and also in Social Studies and Humanities (major “Tourism”), natural science (profession of “Technician-analyst”) and art (lacquer miniature painting on papier-mache) directions, were proposed. The professional activity of teachers was studied in functions of the activity, the actions of teachers and their competencies. The studies conducted and their results are important for the development of theoretical approaches and principles in Professiology of vocational education that will effectively examine the professionalism of specialists, bachelors and masters and will help to build the interrelation between the professional activity and vocational education. The pedagogical means of questionnaires and observations developed and applied in the study, develop the means of diagnosing a teacher’s activity and can be used in procedures for monitoring the vocational education quality and certifying the teaching staff. Keywords: study, activity, teachers, art and pedagogical direction of education, lacquer miniature painting JEL Classifications: I290, I230, Z110